Death at a country mansion - Innes, Louise R. (Innes, Louise R. Daisy Thorne mystery., 2020)
"Welcome to Daisy Thorne's Ooh La La hair salon in the charming village of Edgemead in Surrey, England, where you'll find the latest styles, the juiciest gossip -- and the most tantalizing murder clues... No one would ever accuse famous opera star Dame Serena Levanté of lacking a flare for the dramatic. Unfortunately, it's curtains down on the dysfunctional diva when she's found dead at the bottom of a staircase in her elegant home. Solving an opera singer's murder may not be the typical hairdresser's aria of expertise. But Dame Serena was the mother of Daisy's best friend Floria, so Daisy must do-or-dye her best to get to the roots of the case."--